Determinants of Social Distancing Among South Africans From 12 Days Into the COVID-19 Lockdown: A Cross Sectional Study - Sewpaul, Ronel; Mabaso, Musawenkosi; Dukhi, Natisha; Naidoo, Inbarani; Vondo, Noloyiso; Davids, Adlai Steven; Mokhele, Tholang; Reddy, Sasiragha Priscilla (Frontiers in Public Health, 2021)
Introduction: Social or physical distancing has been an effective measure for reducing the spread of COVID-19 infections. Investigating the determinants of adherence to social distancing can inform public health strategies to improve the behaviour. However, there is a lack of data in various populations. This study investigates the degree to which South Africans complied with social distancing during the country’s COVID-19 lockdown and identifies the determinants associated with being in close contact with large numbers of people. Materials and methods: Data was collected from a South African national online survey on a data free platform, supplemented with telephone interviews. The survey was conducted from 8-29 April 2020. The primary outcome was the number of people that participants came into close contact with (within a 2-metre distance) the last time they were outside their home during the COVID-19 lockdown. Multivariate multinomial regression investigated the socio-demographic, psychosocial and household environmental determinants associated with being in contact with 1-10, 11-50 and more than 50 people. Results: Of the 17,563 adult participants, 20.3% reported having not left home, 50.6% were in close physical distance with 1-10 people, 21.1% with 11-50 people, and 8.0% with >50 people. Larger household size and incorrect knowledge about the importance of social distancing were associated with being in contact with >50 people. Male gender, younger age and being in the White and Coloured population groups were significantly associated with being in contact with 1-10 people but not with larger numbers of people. Employment, at least secondary school education, lack of self-efficacy in being able to protect oneself from infection, and moderate or high risk perception of becoming infected, were all associated with increased odds of close contact with 1-10, 11-50 and >50 people relative to remaining at home. Conclusion: The findings identify subgroups of individuals that are less likely to comply with social distancing regulations. Public health communication interventions and policy can be tailored to address these determinants of social distancing.